Assessing adaptation measures on agricultural water productivity under climate change : a case study of Huai River Basin, China - Dai, Chaoyan (2021)
This study explored an integrated framework to assess the effectiveness of adaptation measures on the water productivity (WP) of the agricultural water management (AWM) system in the Huai river basin of China considering climate change impact. The adaptation measures include optimization of cropping pattern (OCP) and upgradation of irrigation techniques (UIT). The delta change method was used to downscale the climate variables from RCP4.5 and RCP8.5 of general circulation models (GCMs) during 2021-2050, the water footprint theory was used to estimate the spatial distribution of blue water to calculate the WP, and the nonlinear optimization model was used to seek optimal cropping pattern aiming at maximizing the system's WP. The changes in WP due to climate change and adaptation measures (e.g. combinations of OCP and UIT) were compared. Results indicated that WP under RCP4.5 and RCP8.5 would be 4.56% and 6.51% lower than those under the benchmark scenario, respectively. The mitigation rates to the negative impact of climate change on WP under RCP4.5 and RCP8.5 would be (1) 3.05% and 3.37% for the combination of spay irrigation technique and OCP, and (2) 4.34% and 4.59% for the combination of drip irrigation technique and OCP, respectively. It was revealed that the combination of drip irrigation and cropping pattern optimization could largely offset the adverse effect from climate change on WP under RCP4.5. Under such a scenario, the total plant areas of wheat and maize would reduce over the basin and so would the net export of crops in the basin; this would lead to a decrease in the crop trade benefit of 7.07 × 109 $ and a relief of 7.50 × 109 m3 of blue water loss. This study results could offer strategic decision support for long-term sustainable AWM of Huai river basin in a changing environment.